Learning Arabic speaking based on standard skills through a mobile gamification approach / Bashasunnahar Puasa - Puasa, Bashasunnahar (2022)
The 21st century, smartphones have become a necessity in human life where it is used for various purposes, including learning. The current technological advancement has also seen the incorporation of the gamification element as a new norm in learning. This is evidenced by the availability of mobile applications that can be downloaded and used by students to facilitate learning. Past studies reported that the mastery of Arabic speaking skills among Malaysian university students is below the international standard due to reasons like the lack of motivation and exposure. Therefore, this study aims to develop a prototype of a mobile application (i-Kalam App) that can be used for the learning of Arabic speaking skills based on the CEFR standard through the mobile gamification approach model. The development of this prototype application was based on the Horton development model that comprises four phases, namely Phase I: Needs Analysis, Phase II: Design, Phase III: Development, and Phase IV: Evaluation. A mix-method design was used involving the use of questionnaires and structured interviews. The sample comprised 196 users from Akademi Pengajian Bahasa, Universiti Teknologi MARA and ten experts from several local and private universities. The usability evaluation results showed that both experts (M = 4.43) and users (M = 4.35) were satisfied with the technological, usability, and pedagogical aspects of the i-Kalam App. Results from the structured written interview with the experts also showed that the application complied with the CEFR standards, the incorporated gamification elements were appropriate, and the overall application was good. The prototype development should therefore be completed in the future for the benefit of both teachers and students. The findings of this study hope to contribute theoretical and practical implications in the effort of enhancing Arabic language education in Malaysia.